2016
DOI: 10.1007/s12015-016-9676-2
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and in Vitro Differentiation Profile of Human Embryonic Stem Cell Derived NKX2.1-Positive Neural Progenitors

Abstract: The generation of inhibitory interneuron progenitors from human embryonic stem cells (ESCs) is of great interest due to their potential use in transplantation therapies designed to treat central nervous system disorders. The medial ganglionic eminence (MGE) is a transient embryonic structure in the ventral telencephalon that is a major source of cortical GABAergic inhibitory interneuron progenitors. These progenitors migrate tangentially to sites in the cortex and differentiate into a variety of interneuron su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Quantitative measurements of mRNA expression were performed using the 7300 Real Time PCR System (Applied Biosystems) as previously described [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative measurements of mRNA expression were performed using the 7300 Real Time PCR System (Applied Biosystems) as previously described [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of the transcriptomes comparing NKX2.1-positive and NKX2.1-negative populations using shotgun mRNA sequencing (RNA-seq) was performed as previously described [ 12 ]. RNA-Seq data from the BrainSpan Atlas of the Developing Human Brain ( http://brainspan.org ) was assessed as previously described [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have focused on purified, fate-determined populations of hESCs for transplantation. Treating hESCs with the signalling molecule sonic hedgehog (SHH) or a sonic hedgehog agonist (SAG), in combination with modulating the WNT and FGF signalling pathways, can be used in vitro to induce ventral forebrain neural fates and MGE-like cell types [97][98][99][100][103][104][105][106]. Ventralized hESC-derived progenitors have identities similar to that of mouse MGE-derived GABAergic interneuron progenitors, potentially allowing the large-scale in vitro production of human cells for therapies to treat clinical disorders [94].…”
Section: Transplantation Therapy Using Human Embryonic Stem Cell-derimentioning
confidence: 99%
“…To identify gene candidates with expression profiles similar to NKX2.1 that could also help specify the MGE lineage, we utilized previously published data from our laboratory comparing the RNAseq-based transcriptome of FACS isolated human embryonic stem cell (hESC) -derived NKX2.1-positive progenitors to NKX2.1-negative cells. This analysis showed that the profile of surfactant associated 3 ( SFTA3 ) expression closely followed NKX2.1 , suggesting it was a novel MGE marker that could be involved in interneuron specification (12).…”
Section: Introductionmentioning
confidence: 96%